“and now we’re here: the Plasticene”: Ecological Awareness in Margaret Atwood’s Recent Poetry Collection, Dearly - Merve Altın (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Dearly, first published in 2020, is the latest poetry collection of the acclaimed writer, Margaret Atwood. In Dearly, Atwood revisits some of her favourite themes and subjects such as love, loss, time, ageing, sexuality, gender, nature, and environment. The book is divided into five sections, and the poems grouped in the same section revolve around a common theme. In section IV, the poems grouped under the title of “Plasticene Suite” discuss the increasing amount of plastic waste as the distinctive anthropogenic marker of our age. Accordingly, each poem focuses on a different aspect and consequence of this environmental problem. The primary objective of this study is to analyse Plasticene Suite poems, namely “Rock-Like Object on Beach”, “Faint Hopes”, “Foliage”, “Midway Island Albatross”, “Editorial Notes”, “Sorcerer’s Apprentice”, “Whales”, “Little Robot”, and “The Bright Side” from Dearly through the lens of ecopoetry to reveal Atwood’s criticism of the anthropogenic factors contributing to the current ecological crisis, particularly the ever-increasing generation of plastic waste, and to comment on contemporary poetry’s awareness of and power to address the pressing environmental issues. The study also contends that ecopoetic readings of Plasticene Suite poems can help raise awareness about the rise in plastic waste during and after the initial phase of the COVID-19 pandemic. In that sense, the ecopoetic readings of Plasticene Suite poems can urge us to reconsider our dependence on plastic and encourage us to adopt sustainable practices and habits by promoting consciousness about this pressing environmental problem.